Barriers to Contraceptive Use Among Urban Adolescents and Youth in Conakry, in 2019, Guinea - Dioubaté, Nafissatou; Manet, Hawa; Bangoura, Charlotte; Sidibé, Sidikiba; Kouyaté, Mariama; Kolie, Delphin; Ayadi, Alison M. El; Delamou, Alexandre (Frontiers in Global Women's Health, 2021)
Background: Despite efforts to improve access to family planning, contraceptive prevalence remains relatively low among adolescents and youth in Guinea. The objective of this study was to understand the barriers to the use of modern contraceptive methods among urban adolescents and youth (15–24 years) in Conakry, Guinea. Methods: This was a qualitative study using an exploratory design. It was conducted in the capital city of Guinea, Conakry in 2019. Respondents included adolescents and youth aged 15–24 years, health care providers, and parents of adolescents and youth. In-depth individual interviews (IDIs) and focus group discussions (FGDs) were used to collect the data. Sixty IDIs and ten FGDs were planned in Conakry. These data were recorded and transcribed, when applicable, from the local languages into French in an anonymous manner. The data were analyzed using a mixed (inductive and deductive) thematic approach following the elements of the socio-ecological model. Results: Overall, 56 IDIs and 10 FGDs were conducted with 136 participants and included in this analysis. Respondents were adolescents (16%), youth (30%), and key informants (54%) who were health care providers (public and private), decision-makers, parents of adolescents and youth, and neighbors. Among adolescent respondents, 75% were female, and of the youth, 61% were female. Our analysis indicates various and interrelated barriers that limit the access and use of contraceptives by adolescents and youth. These included the individual (fear of side effects, cost, and rumor-related misinformation), interpersonal or family (spouse perception and sexuality taboo and perception of sexual activity before marriage), sociocultural (religious prohibitions and ethnicity), and health care system (breakdown of contraceptive methods in public health facilities, perception of service delivery, provider attitudes, visiting hours, geographic proximity of services, and quality of training received by health care providers) barriers. Conclusion: In our context, the use of modern contraceptive methods by adolescents and youth is influenced by an interaction of various barriers, including individual, interpersonal, sociocultural, and health care system factors. Strengthening contraceptive uptake interventions by involving different stakeholders, including adolescents, parents, religious, and community leaders, and improving the quality of sexual and reproductive health services would help in reducing barriers to contraceptive use among adolescents and youth.